A multi-dimensional description of Subject assignment in English: A corpus-based study - Rodríguez Juárez, Carolina (Adam Mickiewicz University, 2006)
The accessibility of terms to the grammatical operation of Subject assignment seems to be constrained by properties which can predict their level of accessibility to this function and which are organised in a hierarchical fashion. The relevance of such feature hierarchies has been stressed in the theory of Functional (Discourse) Grammar, and it is within this framework that the present research has been conducted. Thus, it has been my main concern to test the validity of each of these priority hierarchies in the process of Subject assignment and to provide a descriptive analysis of the different factors determining Subject selection with regard to a particular language, namely English, by analysing a corpus sample of written English and by observing whether different levels of dominance could be determined among the relevant priority hierarchies both in active and passive constructions. On the basis of the results obtained, a new level of hierarchical organization has been suggested as regards these constructions, by presenting a hierarchy of hierarchies (the Prioritising Hierarchy) which describes the different degrees of fulfilment of these hierarchies in the accessibility of terms to Subject assignment in the English language.